Juridical Analysis Of The Effectiveness And Security Of Autogate In The Enforcement Of Immigration Law In Indonesia (A Research Study In Batam City) - Tresya Millerezki Zebua; Ramlan Ramlan; Darwis Anatami (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Implementing the Autogate system at the Batam Centre Immigration Checkpoint (TPI) is part of the modernisation of the immigration service system that aims to improve efficiency and security in monitoring the entry and exit of people in border areas. However, the effectiveness and reliability of this system still leave legal and technical issues, such as biometric data verification gaps, the absence of specific technical regulations, and limited human resources and infrastructure. This study aims to analyse the legal arrangements and implementation of the Autogate system in supporting the immigration inspection process, evaluate its security in preventing immigration law violations, and examine the obstacles and implications for law enforcement and protection of state sovereignty in border areas, especially in Batam City. The methods used are normative juridical and empirical juridical approaches, with data collection techniques through literature studies and direct interviews with immigration officers at TPI Batam Centre. The analysis was conducted using the framework of justice theory (John Rawls), legal system theory (Lawrence M. Friedman), and legal certainty theory (Sudikno Mertokusumo). The result shows that normatively, the Autogate system has a legal basis in Law No. 6 of 2011 and Minister of Law and Human Rights Regulation No. 9 of 2024. However, there is still a lack of technical operational regulation. Empirically, the system has been proven to improve inspection efficiency, but faces security challenges such as the risk of identity forgery and technical glitches. The research recommends regulatory harmonization, technology strengthening, and officer capacity building so that Autogate truly becomes an effective and legitimate instrument in supporting immigration law enforcement and maintaining state sovereignty.